Economics for as / Colin Bamford. - Bamford, Colin (U K : Cambridge University, 2000)
Economics for AS matches the requirements of the new OCR economics specifications. In one volume,this definitive text provides all the information students need for the AS (advanced subsidiary) units 'The market system','Market failure and government intervention', and 'The national and international economy
includes glossary and index.
Keywords: Economics